Assessment of Career Planning as Predictor of Employee Performance: The Role of Perceived Career Opportunity (Sains Humanika, 2020)
Encouraging employees to put more effort towards achieving organizational goals through good career planning practice has been the focus of many studies. Nevertheless, examining the fundamental reasons why and how career planning/development practice predict performance remains unclear. This study, examined the direct and indirect relationships between career planning/development practice with employee performance (task and contextual) through the mediation of perceived career opportunity. Using a cross sectional survey of 265 employees of 27 local governments in North Western Nigeria, the results of Partial Least Square-Structural Equation Modeling (PLS SEM) revealed that career planning practice predicts employee task and contextual performance and perceived career opportunity was found to have mediated the relationships.
Keywords: Career planning; Career opportunity; Task performance; Contextual performance; Nigeria